Restoring the spirit of [accounting] education using Al-Attas' and Al-Faruqi's thoughts - Febriansyah, Ari; Krisno Septyan (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Current accounting education is inseparable from the idea of secularism, which can mislead the actual goals of [accounting] education. This study aims to offer civilized accounting education to free students [accounting] from secularism. The method used is the thoughts of Syed Naquib al-Attas and Ismail Raji al-Faruqi, which are sourced from the ontological synchronicity research method between researchers and thinkers. The results of this study state that to form a civilized accounting education concept, three steps can be taken, namely 1) making the Qur'an the basis and pinnacle of science, 2) Islamization of science, and 3) Integrating Islamic science into the accounting education curriculum. The ideas of previous thinkers regarding the dignity of science became the source of the formation of a more civilized accounting education concept. This study can answer the concerns about current accounting education by implementing adab as the formation of accountant character so that, in practice, later accountants can carry out their roles as humans who obey Allah SWT